Biological effect of Americium-241 in different types of bacteria - Riah, Khalid Ibrahim; Khalel, Sarab Hussen (Al-Qadisiyah Journal of Pure Science, 2017)
In this study, five types of bacterial cells was exposed to radiation from Am-241. There was a difference between these cells in growth reduction after exposed to radiation . The comparison between the control group and the test group show a significant difference for Escherichia coli and Staphylococcus aureus, but there was no significant difference between them for the other types like Pseudomonas aeruginosa, Proteus spp. and Streptococcus spp. The inhibition in growth of Escherichia coli and Staphylococcus aureus is related to the type of radiation used, the time of exposing and type of bacteria used.